Assessing the current state of ecological connectivity in a large marine protected area system. Issue 2 (5th September 2020) - Roberts, Kelsey E.; Cook, Carly N.; Beher, Jutta; Treml, Eric A.
Abstract: The establishment of marine protected areas (MPAs) is a critical step in ensuring the continued persistence of marine biodiversity. Although the area protected in MPAs is growing, the movement of individuals (or larvae) among MPAs, termed connectivity, has only recently been included as an objective of many MPAs. As such, assessing connectivity is often neglected or oversimplified in the planning process. For promoting population persistence, it is important to ensure that protected areas in a system are functionally connected through dispersal or adult movement. We devised a multi‐species model of larval dispersal for the Australian marine environment to evaluate how much local scale connectivity is protected in MPAs and determine whether the extensive system of MPAs truly functions as a network. We focused on non‐migratory species with simplified larval behaviors (i.e., passive larval dispersal) (e.g., no explicit vertical migration) as an illustration. Of all the MPAs analyzed (approximately 2.7 million km 2 ), outside the Great Barrier Reef and Ningaloo Reef, <50% of MPAs (46‐80% of total MPA area depending on the species considered) were functionally connected. Our results suggest that Australia's MPA system cannot be referred to as a single network, but rather a collection of numerous smaller networks delineated by natural breaks in the connectivity of reef habitat. Depending on the dispersal capacity of the taxa of interest, there may be between 25 and 47 individual ecological networks distributed across the Australian marine environment. The need to first assess the underlying natural connectivity of a study system prior to implementing new MPAs represents a key research priority for strategically enlarging MPA networks. Our findings highlight the benefits of integrating multi‐species connectivity into conservation planning to identify opportunities to better incorporate connectivity into the design of MPA systems and thus to increase their capacity to support long‐term, sustainable biodiversity outcomes. Abstract : Article impact statement : Numerous marine protected areas around Australia are not performing as a functionally connected network. Abstract : Valoración del Estado Actual de la Conectividad Ecológica en un Sistema Extenso de Áreas Marinas Protegidas Resumen: La creación de áreas marinas protegidas (AMP) es un paso muy importante para asegurar la persistencia de la biodiversidad marina. Aunque el área protegida dentro de las AMP está creciendo, el movimiento de individuos (o larvas) entre las AMP, denominado conectividad, sólo ha sido incluido recientemente como un objetivo para muchas AMP. Por lo anterior es normal que con frecuencia se ignora la evaluación de la conectividad o se sobresimplifica durante el proceso de planeación. Para promover la persistencia poblacional es importante asegurar que las áreas protegidas en un sistema estén conectadas funcionalmente por medio de la dispersión o el movimiento de individuos adultos. Diseñamos un modelo multiespecie de la dispersión larval para el ambiente marino australiano y así evaluar cuán protegida está la conectividad a escala local en las AMP y determinar si el sistema extensivo de AMP realmente funciona como una red. Nuestro diseño se enfocó en especies no migratorias con comportamientos larvales simplificados (es decir, dispersión larval pasiva) (p. ej.: sin migración vertical explícita) como un ejemplo. De todas las AMP analizadas (aproximadamente 2.7 millones de km 2 ), fuera de la Gran Barrera de Arrecifes y el Arrecife Ningaloo, <50% de las AMP (46‐80% del área total de la MPA dependiendo de la especie considerada) estaba conectado funcionalmente. Nuestros resultados sugieren que el sistema de AMP australiano no puede ser considerado como una sola red sino más bien como una colección de numerosas redes más pequeñas delineadas por interrupciones naturales en la conectividad del hábitat arrecifal. De acuerdo con la capacidad de dispersión del taxón de interés, puede haber entre 25 y 47 redes ecológicas individuales distribuidas a lo largo del ambiente marino australiano. La necesidad de primero evaluar la conectividad natural subyacente de un sistema de estudio previo a la implementación de nuevas AMP representa una prioridad de investigación clave para aumentar estratégicamente las redes de AMP. Nuestros resultados resaltan los beneficios de la integración de la conectividad multiespecie dentro de la planeación de la conservación para identificar las oportunidades que mejor incorporen la conectividad en el diseño de los sistemas de AMP y así incrementar su capacidad para soportar resultados sustentables de biodiversidad a largo plazo. 摘要: 建立海洋保护区是确保海洋生物多样性长期续存的关键步骤。虽然海洋保护区的覆盖范围在不断扩大, 但海洋保护区之间动物个体 (或幼体) 的运动情况 (即连接度) 在最近才被纳入许多海洋保护区的保护目标之中。因此, 规划过程中往往会忽视或过度简化对连接度的评估。为了促进海洋生物的种群续存, 确保系统中的保护区可以通过生物个体扩散或成体运动来实现功能性连接是十分重要的。本研究设计了一个澳大利亚海洋环境中幼体扩散的多物种模型, 以评估海洋保护区在局域尺度的连接度保护, 并确定大范围的海洋保护区系统是否真正起到了保护网络的作用。我们聚焦于幼体行为简单的非洄游物种, 如没有明显垂直迁移的被动幼体扩散的物种, 以作为例证。在我们分析的所有海洋保护区中 (约 270 万平方公里), 位于大堡礁和宁格罗礁之外的海洋保护区只有不到 50% 是功能性连接的, 占海洋保护区总面积的 46‐80% (取决于纳入考虑的物种) 。我们的研究结果表明, 澳大利亚海洋保护区系统不能被视为一个单一的网络, 而是由许多较小的网络组成的集合, 这些网络由珊瑚礁栖息地之间的自然隔断所划分。我们基于研究关注类群的扩散能力分析得出, 澳大利亚海洋环境中可能分布着 25 到 47 个独立的生态网络。因此, 在建立新的海洋保护区之前, 应首先评估研究系统潜在的自然连接度, 这是战略性扩大海洋保护区网络的研究关键点。我们的研究结果还突出了将多物种连接度纳入保护规划的好处, 这样有助于更好地将连接度纳入海洋保护区系统的设计, 从而提高其支持长期、可持续的生物多样性保护成果的能力。【翻译: 胡怡思; 审校: 聂永刚】